ROLE OF LEARNING PPKN TO IMPROVING STUDENTS CIVIC DISPOSITION IN SENIOR HIGH SCHOOL - Rahmatiani, Lusiana; Nugraha, Yogi; Sari, Puspita (International Journal of Psychosocial Rehabilitation, 2020)
Education serves to empower the human potential to inherit, develop and build the culture and civilization of the future. Citizenship education is common subjects are the rights for all students to get and is the school’s obligation to load the Civic Education curriculum. The statement in accordance with the mandate of the Law of the Republic of Indonesia that citizenship education stipulated in Law No. 2 of 1989 on the national education system, section 39 has determined that the content of the curriculum of every kind, lines and levels of education must include Pancasila education, religious education and civic education. The progress of a nation depends heavily on the quality of education, not only the quality of education that makes a nation forward. There are other things that factor into supporting a nation can move forward, namely the quality of the personality and character of the nation itself, namely civic disposition. The research was done in high school. The purpose of this study mendeskripsikan Civics learning how to improve students’ civic disposition. The research method used is a qualitative method of data collection techniques, observation, interviews and documentation.